2017
DOI: 10.1186/s12974-016-0782-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced neuroinflammation mediated by DNA methylation of the glucocorticoid receptor triggers cognitive dysfunction after sevoflurane anesthesia in adult rats subjected to maternal separation during the neonatal period

Abstract: BackgroundMounting evidence indicates that children who experience abuse and neglect are prone to chronic diseases and premature mortality later in life. One mechanistic hypothesis for this phenomenon is that early life adversity alters the expression or functioning of the glucocorticoid receptor (GR) throughout the course of life and thereby increases sensitivity to inflammatory stimulation. An exaggerated pro-inflammatory response is generally considered to be a key cause of postoperative cognitive dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 60 publications
(61 reference statements)
1
79
1
1
Order By: Relevance
“…2, 28 Gong has described that sevoflurane exposure impaired spatial memory in aged rats by increasing inflammation. 30 On the other hand, the elevated antioxidant defence and apoptosis status were also observed in blood samples of sevoflurane-administered children. 30 On the other hand, the elevated antioxidant defence and apoptosis status were also observed in blood samples of sevoflurane-administered children.…”
Section: Discussionmentioning
confidence: 99%
“…2, 28 Gong has described that sevoflurane exposure impaired spatial memory in aged rats by increasing inflammation. 30 On the other hand, the elevated antioxidant defence and apoptosis status were also observed in blood samples of sevoflurane-administered children. 30 On the other hand, the elevated antioxidant defence and apoptosis status were also observed in blood samples of sevoflurane-administered children.…”
Section: Discussionmentioning
confidence: 99%
“…Since DNA methylation shows functions because of its ability of regulating genes expression (Bansal and Pinney, 2017), neurological diseases-related DNA hypomethylation or hypermethylation may be the results of the alteration of functional biomolecules mediated by some altered certain genes expression. Zhu Y et al reported that hypermethylation of a certain DNA promoter up-regulated neuroinflammation after sevoflurane anesthesia in animal-model of endoplasmic reticulum stress occurred during the neonatal period (Zhu et al, 2017). Although no proof associated with hypomethylation of DNA, it gives some support for the viewpoint of DNA hypermethylation in neurological damage after sevoflurane anesthesia at least in part.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, presence of leukotriene E4 might hint that prenatal exposure to sevoflurane caused neuroinflammation in offspring. Meanwhile, since inflammatory genes were regulated by methylation in neurodegenerative diseases (Nicolia et al, 2017), it was plausible that methylation served as a crucial role between neuroinflammation and neurotoxicity, and this assumption has been partially confirmed (Zhu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, DNA methylation is essential for regulating synaptic plasticity in hippocampal neurons, thereby influencing learning and memory . Furthermore, epigenetic mechanisms strongly influence the regulation of neuroinflammation, which underlies the development of POCD . However, data in support of an association between global DNA methylation and changes in cognitive function in patients with POCD are not available.…”
Section: Introductionmentioning
confidence: 99%